Nervous fictions : literary form and the enlightenment origins of neuroscience - Keiser, Jess, 1984- (University of Virginia Press, 2020)
"Nervous Fictions looks at early writing on the brain and figurative language. It argues that as more became known about the brain and nervous system in the seventeenth and eighteenth centuries, new literary technologies needed to be developed to describe body and mind"--